MEMBANGUN KELOMPOK SADAR WISATA DALAM PENGEMBANGAN POTENSI DESA SEBAGAI DESA WISATA DI DESA CEPAKA KECAMATAN KEDIRI KABUPATEN TABANAN - Ni Made Hartini; Ni Made Ernila Junipisa (Synergy and Society Service, 2021)
Cepaka Village is one of the villages located in the Kediri sub-district, Tabanan Regency. The area has a wide expanse of rice fields and people who are still full of agriculture. The dominant community working in the agricultural and tourism sectors is a village that has the potential to be developed into a tourist village supported by the creative economy. In Community Service Activities in Cepaka Village, Kediri, Tabanan The targets to be achieved are the formation of a Tourism Awareness group as a driver and manager of a tourist village by the local community; Village potentials that have uniqueness and beauty and community creativity can be prepared and packaged as tourist attractions in the development of tourist villages in Cepaka village; The creation of village environmental conditions according to the requirements of a tourist village, namely Sapta Pesona (safe, clean, orderly, beautiful, cool, friendly, and memorable). The method of implementing the PKM program, namely conducting socialization, debriefing and assistance to the Cepaka village community who have awareness of tourism activities. The results achieved in the PKM program are guiding in designing a proposal for the formation of a Tourism Awareness Group submitted by the community with an introduction from the Prebekel to be submitted to the Tabanan Regency Tourism Office. The proposal section consists of the background of developing a tourist village, the potentials to be developed as a tourist village, Vision, Mission and objectives of developing the village as a tourist village. The community is aware of its role and responsibility as a good host for guests or tourists who visit to create a conducive environment and atmosphere as stated in the slogan Sapta Pesona..